Comparison Of The Pretrial System In Indonesia And The US - Haeranah, Haeranah; Achmad Dzulfikar Musakkir; Jims Oktovianus; Miftah Idris (Cita konsultindo, 2023)
The pretrial system in Indonesia and in America clearly has differences based on the state legal system in each of these countries. In Indonesia, the implementation of pretrial is clearly regulated in the Criminal Procedure Code, while in America, which has a decentralized legal system, where the stages are regulated by federal and state laws which may differ in all jurisdictions in America. To find out comprehensively the comparison in the pretrial system that exists in Indonesia and America, so the research method used in this study is normative legal research with a comparative approach. From the research results, it was found that the outline of the comparison of the pretrial system between the two countries, such as the process of arrest and detention, as well as the concepts of bail and pretrial release, showed variations between the two countries. Indonesia uses the temporary release option, while the United States generally uses bail and conditional release mechanisms. Motions and pretrial hearings in Indonesia involve pretrial procedures, which focus on examining the legality of enforcement actions, while the United States allows pretrial motions and hearings on a variety of issues. Finally, the right to legal counsel is recognized in both countries, although provisions regarding public defenders may differ.